PERLINDUNGAN HUKUM TERHADAP DIREKSI YANG DIBERHENTIKAN TANPA MELALUI RAPAT UMUM PEMEGANG SAHAM (Studi Pada PT. Sumber Andalan Mandiri (SAM)) - Lubis, Ikhsan; Oktarina, Neneng (LPPM Universitas Ekasakti Padang, 2018)
One of the most incorporated legal entities as a business entity by business people today is a Limited Liability Company. In practice the mechanism for the appointment, replacement, and dismissal of the Board of Directors is not always adhered to properly by the Company's organs. In the case of PT. SAM with Phiedi as Director of PT. SAM has permanently and permanently dismissed one member of the Board of Directors from his position as a director without going through the GMS. Legal facts, the existence of e-mail dated April 22 and 24 2014 which essentially contained the dismissal of the Directors of PT. SAM is permanent or permanent. This paper discusses several problem formulations, namely: 1) What is the legal protection of directors who are dismissed without going through a general meeting of shareholders according to the positive legal framework in Indonesia? 2) What is the legal effort made by the directors who are dismissed without going through a general meeting of shareholders? This research is a descriptive research. The approach used in this study is a normative juridical approach supported by an empirical juridical approach. The data used in this study are secondary data and primary data. Against all data and materials obtained from the results of the study will be compiled and analyzed qualitatively. The results of the study explain that legal protection against directors who are replaced by directors who are dismissed without going through the GMS then: 1) Each member of the board of directors is personally responsible for the loss of the company; 2) Personal responsibility is attached to the member of the board of commissioners if he is guilty or negligent in carrying out the duties of supervision or giving advice; 3) Although the loss arises from the management of the board of directors, the members of the board of commissioners remain personally responsible if in the supervision of the implementation of the management of the board of directors there is an element of error or negligence of the board of commissioners; and 4) The extent of personal responsibility of the members of the board of commissioners, limited to their mistakes or negligence, and fifth, if the members of the board of commissioners consist of 2 (two) or more, personal responsibility, is jointly responsible for each member of the board of commissioners. Legal efforts made by directors who are dismissed without going through a general meeting of shareholders, then upon dismissal of the Board of Directors without the GMS, the Commissioner must immediately convene an Extraordinary General Meeting of Shareholders to follow up on the temporary dismissal of the Board of Directors by the Board of Commissioners, then as soon as possible the Board of Commissioners calls the shareholders in the framework of the Extraordinary GMS to strengthen its decision. Considering that the Director is a majority shareholder, of course the ordinary GMS will not succeed because there is a quorum rule and the validation of the vote